Lesion of the major sciatic nerve due to a shotgun projectile - Luis Enrique Montoya Cardero; Mileidys León Piñeiro; Pedro Armando Candeau Tamayo (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a 26 years patient is described. He was assisted in the Orthopedics and Traumatology Service of Salvador Allende Integral Diagnostic Center from Caracas, in the Bolivian Republic of Venezuela who had received a shotgun shot in the posterior face of both thighs 6 months ago. This time he went to visit the doctor with intense pain in the left inferior member, mainly below the knee, accompanied by paresthesias in the innervation area of both bifurcation branches of the sciatic nerve. It could be demonstrated that the young man presented multiple projectile impacts in the posterior face of both thighs and halting march. The radiographic studies confirmed the presence of 8 projectiles, two in the right thigh and 6 in the left one. In the lateral view it was observed that one of them was at a depth that matched with the anatomical region of the left sciatic nerve. Local anesthesia, sedation and an images intensifier were used for the operation. The projectile located in the epineurium of the sciatic nerve could be removed with the patient cooperation without complications. After 3 months the discomfort had disappeared and he could return to his usual activities.